Greenhouse Gas Trading Scheme in the Republic of Kazakhstan - Seven Years from Its Creation, Problems and Solutions - KOZHIKOV, Marat; KAPSALYAMOV, Bauyrzhan (Journal of Environmental Management and Tourism, 2022)
The article studies the greenhouse gas trading scheme in the Republic of Kazakhstan. The research analyzes an international experience in the sphere of greenhouse gas emissions trading and identifies the main provisions which are fundamental for the efficient work of emissions trading schemes. The work of the Kazakhstan greenhouse gas trading scheme was examined through these key provisions. Materials represent the work of emissions trading schemes in several countries, and, particularly, in the Republic of Kazakhstan. For a more detailed study, further directions were proposed to improve the work of the emissions trading scheme.